Long-Term Non-Progression and Broad HIV-1-Specific Proliferative T-Cell Responses - Imami, Nesrina; Westrop, Samantha J.; Grageda, Nathali; Herasimtschuk, Anna A. (Frontiers in Immunology, 2013)
Complex mechanisms underlying the maintenance of fully functional, proliferative, HIV-1-specific T-cell responses involve processes from early T-cell development through to the final stages of T-cell differentiation and antigen recognition. Virus-specific proliferative CD4 and CD8 T-cell responses, important for the control of infection, are observed in some HIV-1+ patients during early stages of disease, and are maintained in long-term non-progressing subjects. In the vast majority of HIV-1+ patients, full immune functionality is lost when proliferative HIV-1-specific T-cell responses undergo a variable progressive decline throughout the course of chronic infection. This appears irreparable despite administration of potent combination antiretroviral therapy, which to date is non-curative, necessitating life-long administration and the development of effective, novel, therapeutic interventions. While a sterilizing cure, involving clearance of virus from the host, remains a primary aim, a “functional cure” may be a more feasible goal with considerable impact on worldwide HIV-1 infection. Such an approach would enable long-term co-existence of host and virus in the absence of toxic and costly drugs. Effective immune homeostasis coupled with a balanced response appropriately targeting conserved viral antigens, in a manner that avoids hyperactivation and exhaustion, may prove to be the strongest correlate of durable viral control. This review describes novel concepts underlying full immune functionality in the context of HIV-1 infection, which may be utilized in future strategies designed to improve upon existing therapy. The aim will be to induce long-term non-progressor or elite controller status in every infected host, through immune-mediated control of viremia and reduction of viral reservoirs, leading to lower HIV-1 transmission rates.